2009
DOI: 10.1080/10903120903144866
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Naloxone Is a Viable Alternative to Intravenous Naloxone for Prehospital Narcotic Overdose

Abstract: The time from dose administration to clinical response for naloxone was longer for the IN route, but the overall time from patient contact to response was the same for the IV and IN routes. Given the difficulty and potential hazards in obtaining IV access in many patients with narcotic overdose, IN naloxone appears to be a useful and potentially safer alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 6 publications
2
50
0
4
Order By: Relevance
“…239 Some patients may require much higher doses to reverse intoxication with atypical opioids, such as propoxyphene, or following massive overdose ingestions. 240,241 Naloxone can be given IV, 235,236,242,243 IM, 232,235,236 intranasally, 232,242 and into the trachea. 244 The duration of action of naloxone is approximately 45 to 70 minutes, but respiratory depression caused by ingestion of a long-acting opioid (eg, methadone) may last longer.…”
Section: Opioid Toxicitymentioning
confidence: 99%
“…239 Some patients may require much higher doses to reverse intoxication with atypical opioids, such as propoxyphene, or following massive overdose ingestions. 240,241 Naloxone can be given IV, 235,236,242,243 IM, 232,235,236 intranasally, 232,242 and into the trachea. 244 The duration of action of naloxone is approximately 45 to 70 minutes, but respiratory depression caused by ingestion of a long-acting opioid (eg, methadone) may last longer.…”
Section: Opioid Toxicitymentioning
confidence: 99%
“…Naloxone has an excellent safety profile and can rapidly reverse CNS and respiratory depression in a patient with an opioid-associated resuscitative emergency. Based on the rescuer's training and clinical circumstance, naloxone can be administered intravenously, [78][79][80][81] intramuscularly, 78,79,82 intranasally, 80,[82][83][84][85][86] or subcutaneously 87 ; nebulized for inhalation 88,89 ; or instilled into the bronchial tree via endotracheal tube. 90 Appropriate dose and concentrations differ by route.…”
Section: S504 Circulationmentioning
confidence: 99%
“…In first in-human trials, nasal naloxone was found to elicit withdrawal symptoms in opioid-dependent volunteers (Loimer et al, 1992(Loimer et al, , 1994. Since the early 2000s, nasal naloxone has been used off-label by ambulance personnel (Barton et al, 2005(Barton et al, , 2002Belz et al, 2006;Kelly et al, 2005;Kerr et al, 2009;Merlin et al, 2010;Robertson et al, 2009;Weber et al, 2012) and in the emergency department (Sabzghabaee et al, 2014). More recently, improvised nasal kits (consisting of a prefilled naloxone syringe and an atomizer which fits onto the syringe to generate a nasal spray) have been provided to opioid users, peers, and families in take-home naloxone trials (Doe-Simkins et al, 2009;Dwyer et al, 2015;Walley et al, 2013aWalley et al, , 2013b, and succesful overdose reversals using improvised nasal kits have also been reported for police first responders (Rando et al, 2015).…”
Section: Sublingualmentioning
confidence: 99%